CLOUD TECHNOLOGIES REVOLUTIONIZING HEALTHCARE: SCALABLE TRANSACTION SYSTEMS FOR PATIENT DATA AND REAL-TIME DIAGNOSTICS - Varshini Choudary Nuvvula, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article examines the transformative impact of cloud computing technologies on healthcare delivery systems, focusing on scalable transaction systems for patient data management and real-time diagnostics. The article explores how cloud-based solutions have revolutionized electronic health records management, improved data accessibility, and enhanced diagnostic capabilities across healthcare facilities worldwide. The article investigates the implementation of advanced security protocols, interoperability frameworks, and artificial intelligence integration in healthcare cloud computing. Through analysis of multiple case studies and industry-wide implementations, the article demonstrates how cloud technologies have fundamentally altered healthcare delivery models, enabling improved patient care outcomes, operational efficiency, and cost-effectiveness while maintaining robust security and compliance standards.